Design and Development of a Solar Thermal Collector with Single Axis Solar Tracking Mechanism - Theebhan M.; Long C.Y.; Tiong T.T. (EDP Sciences, 2023)
Harvesting; Manufacture; Solar collectors; Solar energy; Design and Development; Focal points; Solar thermal; Solar thermal collector; Solar thermal energy; Solar tracker; Solar tracking; Source of energy; Solar heating